Cerebral Microdialysis Monitoring to Improve Individualized Neurointensive Care Therapy: An Update of Recent Clinical Data - Carteron, Laurent; Bouzat, Pierre; Oddo, Mauro (Frontiers in Neurology, 2017)
Cerebral microdialysis (CMD) allows bedside semi-continuous monitoring of patient brain extracellular fluid. Clinical indications of CMD monitoring are focused on the management of secondary cerebral and systemic insults in acute brain injury (ABI) patients (mainly, traumatic brain injury TBI, subarachnoid haemorrhage SAH and intracerebral hemorrhage ICH), specifically to tailor several routine interventions – such as optimization of cerebral perfusion pressure, blood transfusion, glycemic control and oxygen therapy – in the individual patient. Using CMD as clinical research tool has greatly contributed to identify and better understand important post-injury mechanisms – such as energy dysfunction, post-traumatic glycolysis, post-aneurysmal early brain injury, cortical spreading depressions, and sub-clinical seizures. Main CMD metabolites (namely, lactate/pyruvate ratio and glucose) can be used to monitor the brain response to specific interventions, to assess the extent of injury and to inform about prognosis. Recent consensus statements have provided guidelines and recommendations for CMD monitoring in neurocritical care. Here, we summarize recent clinical investigation conducted in ABI patients, specifically focusing on the role of CMD to guide individualized intensive care therapy and to improve our understanding of the complex disease mechanisms occurring in the immediate phase following ABI. Promising brain biomarkers will also be described.